KEPERCAYAAN MASYARAKAT BUGIS PRA ISLAM - Ridhwan Ridhwan (Institut Agama Islam Negeri (IAIN) Bone, 2018)
This article discusses pre-Islamic Bugis community beliefs. There are issues discussed, namely the origins of Bugis society and pre-Islamic Bugis community beliefs. The results of the discussion show that the Bugis people who inhabited more than half of South Sulawesi's territory could be traced to tens of thousands of years before Christ. They are known as a combination of Austro Melanesoid races, Abris Sous Roche, and Paleo Mongoloid that inhabited this island around 40,000 to 30,000 years ago. Then followed by the Austronesians who came around 3000 years BC. come in waves. Their beliefs experience dynamics. At first they may believe that all objects in this nature have magical powers in the form of spirits, so that they can be called adherents of animism and dynamism. However, in subsequent developments there were strong indications that Bugis community trust had influence from Hinduism and Buddhism. This is indicated by the many instillations of the two religious traditions used by the pre-Islamic Bugui community, for example Dewata, Bathara, Sri Sangyang, Bissu, and others. Therefore, some experts say that their beliefs can be referred to as monolatry, or Uhr-Monotheism (ancient monotheism).